Exploring the role of agricultural innovations in the Scottish beef sector: pathways towards more sustainable production - Can, E. (2020)
It is widely recognised that innovation is essential for the development of the agricultural sector. To address this challenge, this thesis has focused on how sustainable agricultural innovation may be delivered at farm-level in Scottish beef production systems. Fostering innovation requires an improved understanding of farmers’ innovative behaviour. Accordingly, farmers’ intentions towards farming in Scotland and their reliability were assessed. A segmentation behavioural model was developed and three classes of farmers were identified (n=213): Profit-seekers (42.1%), Satisfiers (35.7%) and Expansionists (22.1%). This model was subsequently linked to a farm-level economic model to estimate the effects of a set of innovations across the distribution of beef farms, under two alternative agricultural support policy scenarios.